Water Quality and Hydrochemical Studies in Watersheds Cikapundung River Case Study - Peny Supriatno; Rizky Syaputra; Robertho Kadji; Lia Alfianita (Budapest International Research and Critics University, 2022)
Cikapundung River is one of the rivers that plays an important role as a water source in the city of Bandung. This river has great potential to be used as water supply in the city of Bandung. For further utilization, it is necessary to study the quality and hydrochemistry of water in the watershed (DAS), especially in the Cikapundung River. Based on the studies that have been carried out, it was found that the water quality is quite poor. Poor water quality is caused by a continuous process of pollution, which causes changes in the value of the physical and chemical parameters of water in the Cikapundung watershed. This process is further supported by the occurrence of dilution caused by the high intensity of rain in the city of Bandung. According to the graphical representation of the hydrochemistry of water, the type of water in the form of calcium bicarbonate was obtained based on the Piper Diagram. Bicarbonate water comes from the weathering of rocks or minerals near the surface. Supported by graphical representation using Durov Diagram, water in the Cikapundung watershed is intermediate water that has undergone ion exchange. This is evidenced by the Stiff Diagram which groups alkaline earth cations which are larger than alkali metals, and weak acid anions which are larger than strong acid anions. These three graphic representatives provide information about the evolutionary processes that occur in the Cikapundung watershed.